Remote sources for year‐to‐year changes in the seasonality of the Florida Current transport. Issue 10 (18th October 2016) - Domingues, Ricardo; Baringer, Molly; Goni, Gustavo
Abstract: The seasonal variability of the Florida Current (FC) transport is often characterized by the presence of an average annual cycle (8% of the variance) of ∼3 Sv range peaking in boreal summer. However, the seasonality displayed by the FC transport in any individual year may have very distinct characteristics. In this study, the analysis focuses on seasonal changes (73–525 day frequency band) in the FC transport that are associated with a variable annual phase, which is defined as the transient seasonal component (FCt, 27% of the variance). It is shown that the FCt is largely modulated by westward propagating sea height anomaly (SHA) signals that are formed in the eastern North Atlantic 4–7 years earlier than observed at 27°N in the Florida Straits. These westward propagating SHA signals behave approximately like first baroclinic Rossby waves that can modulate changes in the FC seasonal variability upon arrival at the western boundary. The main finding from this study is that changes in coastal sea‐level between 25°N and 42°N linked with westward propagating signals account for at least 50% of the FCt. The integrated changes in the coastal sea‐level between 25°N and 42°N, in turn, drive adjustments in the geostrophic transport of the FC at 27°N. Results reported here provide an explanation for previously reported year‐to‐year changes in the FC seasonality, and suggest that large sea‐level variations along the coast of Florida may be partially predictable, given that these Rossby‐wave‐like signals propagate approximately at fixed rates in the open ocean along 27°N. Key Points: The seasonal variability of the Florida Current (FC) transport exhibits year‐to‐year changes during the 1983–2013 record Year‐to‐year changes in the FC seasonality are linked with westward propagating signals (WPS) originated in the eastern North Atlantic Coastal sea‐level changes forced by WPS account for ∼50% of the FC seasonal variability that is linked with variable annual phase